(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Currently, the global Covid-19 epidemic has been having an impact on the trend of the organization and implementation training activities of higher education. Blended teaching and building a systematic Style-Based Blended teaching model still have certain limitations for teachers. This study has surveyed and evaluated the results of implementing systematic Style-Based Blended teaching model with 135 lecturers from universities in Vietnam from the academic year 2019 - 2020. This study used a combination of qualitative and quantitative methods, the parameters of this research results were verified through evaluating the applied results before and after implementing systematic Style-Based Blended teaching model in teaching at experimental universities. Research results with this Blended teaching model present evidence in implementing and developing a systematic Style-Based Blended teaching model with effective effects on improving teaching performance of teachers, contributing to improve the quality of teaching in higher education.